Monitoring of the effect of solar radiation and rain on the building envelope with integrated vertical vegetation. (December 2022) - Nicolini, Elvira; Germanà, Maria Luisa; Marcon, Giulia; Chiodi, Marcello; Gutiérrez, Álvaro; Olivieri, Francesca
Abstract: The goal of the present paper is the verification of the improvement of the performance of a building envelope with a green wall also in conditions of high irradiance (≥0.6 kW/m 2 ) and with variable meteorological conditions (sunny, cloudy, and rainy), with a focus on intense rainfall and tempest. The object of the analysis has been the Innovation and Technology for Development Center in the University Campus of the Polytechnics of Madrid, where a modular system of integrated vertical vegetation has been installed on the skin of the South and West prospects. The study is based on the analysis of the effective thermoregulation capacity of the system in different climatic situations and has been allowed by a database covering a 3-year period, which contains data from continuous monitoring of the meteorological variations and thermal flows through a weather station and sensors placed on the external surface of the envelope, and on the external and internal surfaces of the wall. The experimentation shows that the use of a green wall on the West prospect is even more valid in conditions of high irradiance, as it allows reducing the temperature of the wall by 10 °C, compared to the scenario without the green wall. The combined effect of rain and solar radiation produces different results on the exposure of the walls, with a visible effect only on the South side. Highlights: Green wall performance in high irradiance and variable meteorological conditions. Database covering a 3-year period with continuous data monitoring through sensors. During high irradiance, in the west, green wall can cool 10 °C less than bare wall. Different results on the exposure of the walls with higher effect on the south side.